The Effect of Service Quality on Tourist Satisfaction in The Implementation of CHSE at Museum Nasional Jakarta - Lyly Soemarni; Harny Huvianta (International Journal of Travel, Hospitality and Events, 2023)
The purpose: of this study was to determine the effect of service quality on the implementation of CHSE on the level of tourist satisfaction in visiting the National Museum in Jakarta. Research Methods: the data used in this study are primary data obtained by distributing questionnaires to visitors of Jakarta National Museum aged 18 years and over and used purposive sampling. The analytical method used is simple linear regression analysis. Result: there are two hypotheses proposed and one is accepted, there is an influence between quality of service in the CHSE implementation toward tourists’ satisfaction. Keywords: CHSE, Tourist Satisfaction, Service Quality.